Development of a bipropellant rocket engine with a focus on the injector - İskender, Enes Oğuz. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Access to space relies on powerful propulsion systems to take a spacecraft out of the Earth’s atmosphere. Currently, chemical propulsion systems are the only propulsion method that are able to provide the thrust levels required to carry out these missions. Among the chemical propulsion systems, bipropellant liquid rocket engines provide the highest specific impulse. In this study, a bipropellant liquid rocket engine, and specifically its injector, is designed, manufactured and tested. The used injector is a fixed area triple impinging injector. The tests include water tests, open injector cold flow tests, open injector hot flow tests and an engine hot fire test. BUSTLab (Boğaziçi University Space Technologies Laboratory) Liquid Rocket Engine is a pressure - fed liquid oxygen - ethanol (75% ethanol - 25% water) engine. The design point for the engine is 5.65kN thrust, 254s of specific impulse, 1.25 oxidizer to fuel ratio, total mass flow rate of 2.27kg/s at 30bar chamber pressure. The engine is hot fire tested at full thrust for 12 seconds. During this test, 0.83kg/ s mass flow rate of oxidizer and 0.89kg/s mass flow rate of fuel are measured which gives 1.72kg/s total mass flow rate and 0.93 oxidizer to fuel ratio. Chamber pressure and thrust measurements during this test are inconclusive due to sealing and load cell issues. With the measured mass flow rates, the chamber pressure is calculated to be 21.2bar and the thrust is calculated as 3.62kN.
Keywords: Rocket engines.; Injectors.